The robustness of future changes in Northern Hemisphere blocking: A large ensemble projection with multiple sea surface temperature patterns. Issue 10 (31st May 2017) - Matsueda, Mio; Endo, Hirokazu
Abstract: Future changes in the frequency of Northern Hemisphere blocking are investigated via large ensemble simulations using a 60 km mesh atmospheric general circulation model prescribed with six future sea surface temperature patterns derived from state‐of‐the‐art climate models under a 4 K warmer climate. Our simulations depict the frequency of wintertime blocking decreasing from 16.6% ± 0.7% to 13.1% ± 2.1% in the Euro‐Atlantic sector and from 17.4% ± 0.7% to 14.8% ± 2.4% in the Pacific sector. This decline in frequency is seen to affect Euro‐Atlantic blocking of all durations and Pacific blocking of more than 15 days' duration. During summer, our simulations not only exhibit a robust decrease (from 10.7% ± 0.4% to 7.6% ± 0.7%) in the Euro‐Atlantic blocking frequency but also show that the magnitude of this decrease is smaller for longer‐lived blocking. In contrast, the Pacific blocking frequency either does not change or increases slightly, particularly for events of 15–29 days' duration. Key Points: Changes in wintertime Pacific (PA) and Euro‐Atlantic (EA) blocking frequencies depend on strength and types of El Niño, respectively Wintertime PA and EA blocking frequency decreases (increases) by 1.7% to 7.1% (0.7%) and 2.6% to 5.8% (0.4%), respectively Summertime EA blocking frequency shows a robust decrease by 2.4% to 4.1%. Long‐lasting blocking events show a less robust decrease